Territorial features of basic food availability in Ukraine in the context of food security analysis - Gavrikov, Artem; Telebienieva, Ievgeniia (Human Geography Journal, 2024)
The article is dedicated to the analysis of territorial peculiarities in the availability of basic food products in Ukraine in the context of food security. The study examines the regional distribution of ten key food products (bread, flour, oil, sugar, potatoes, poultry meat, eggs, lard, milk, frozen fish) and considers the impact of socio-economic and military-political factors on food security levels across different regions of the country. Based on statistical data analysis and geospatial modeling, it has been established that the most favorable conditions for food security are maintained in the central and western regions of Ukraine, where the agro-industrial infrastructure remains developed and logistics chains are relatively stable. In contrast, the eastern and southern regions have suffered significant destruction due to military actions, leading to the destruction of agro-industrial enterprises, a reduction in sown areas, logistical disruptions, and, consequently, a shortage of certain categories of food products. Special attention is given to the impact of internally displaced persons (IDPs) on regional demand and the structure of food consumption. The increase in the number of IDPs in Lviv, Zakarpattia, Chernivtsi, Khmelnytskyi, Dnipropetrovsk, and Kharkiv regions has caused a rise in consumer demand, affecting price formation and food availability. The consequences of the destruction of critical infrastructure, particularly the Kakhovka Hydroelectric Power Plant (HPP), are also examined, as this has led to the flooding of agricultural lands, the loss of irrigation systems, and a decline in crop yields in Ukraine’s southern regions. The study results indicate a significant regional differentiation in food availability. In central regions, prices remain more stable due to substantial local production volumes, while frontline and occupied areas experience an acute shortage of certain food items. Changes in population consumption patterns and disruptions to traditional logistics routes have significantly influenced the territorial availability of food products, which may have long-term consequences for the country’s food security.